Factores sociodemográficos y su relación con los controles prenatales insuficientes en pacientes atendidas en el Centro de Salud Enrique Ponce Luque, en el periodo junio – octubre 2023. - Alban Quinatoa, Nathaly Piedad (2023)
This research project was carried out due to the high rate of patients with insufficient prenatal check-ups and its objective is to identify how this problem has a direct and indirect relationship with certain sociodemographic factors. The data was obtained through the data collection table of the clinical histories, matrices, as well as surveys of pregnant women at the Enrique Ponce Luque Health Center. The results showed that the main sociodemographic factors that are related to insufficient prenatal checkups are: Maternal age, since it was found that pregnant women with an age range of 15 to 19 years represent more than half of the group of patients with less than 5 controls, being 74%, as well as work, since it was found that working patients tend to have a less constant prenatal control follow-up, making up 85% of the group of respondents with insufficient prenatal controls, and as a last factor we have the number of children, where patients with 2 or more children also represent 74% of pregnant women with less than 5 controls. It was also identified that the level of knowledge of pregnant women about prenatal care is low and that among the complications associated with insufficient prenatal care, the most relevant pathology is vaginal infections with a percentage of 45%, followed by urinary tract infections with a percentage of 38%.